Neocrangon orientalis, a new caridean shrimp species (Crustacea, Decapoda, Crangonidae) from the East China Sea - Han, Qingxi; Li, Xinzheng (Zootaxa, 2009)
The Genus Neocrangon Zarenkov, 1965 was one of the most poorly reported genera in the caridean family Crangonidae. Zarenkov (1965) divided the genus Crangon Fabricius, 1758 into two subgenera, ie. Crangon s. str. and his new subgenus Neocrangon, and designed eleven species in the latter, the type species was Crangon communis Rathbun, 1899. Squires and Figueira (1974) followed Zarenkov (1965) and accepted the subgenus Neocrangon. Kuris & Carlton (1977) raised Neocrangon as a separated genus and recognized that only five species, which has two gastric spines as that in the type species from the eleven species designed by Zarenkov (1965), belonging to Neocrangon. The five species were: Neocrangon communis (Rathbun, 1899), N. abyssorum (Rathbun, 1902), N. resima (Rathbun, 1902), N. joloensis (De Man, 1929) and N. zacae Chace, 1937. Then, Wicksten (1996) synonymized N. zacae Chace, 1937 as a junior synonym of N. resima (Rathbun, 1902). Up to date, four species have been recognized in the genus Neocrangon Zarenkov, 1965. When we sorted the crangonid shrimp specimens deposited in the collections of the Institute of Oceanology, Chinese Academy of Sciences, Qingdao (IOCAS), eight specimens belonging to Neocrangon collected by trawling in the China-America Continental Shelf Cooperative Investigation of the East China Sea (1978–1979) were separated out and were identified belonging to an undescribed species. Based on the specimens, we describe a new species in the present paper. The following abbreviations are used in the text: cl, postorbital carapace length; CN, collection number, referring to the preliminary registration number when the specimen(s) was collected; MBM, Marine Biological Museum of the IOCAS.